DIGITIZATION OF HIGHER EDUCATION INSTITUTION - Buinytska, Oksana; Varchenko-Trotsenko, Liliia; Hrytseliak, Bohdan (Educological discourse, 2020)
The article discusses the process of digitization of higher education institution on the example of Borys Grinchenko Kyiv University and analyzes the main aspects of digital campus implementation. The perspective world educational technologies are described which development influences changes of the concept of management in modern educational establishments and in the educational process as a whole. Also described the main legislative decisions that may serve as a basis for transforming a higher education institution into a «digital campus». Regulatory documents of Borys Grinchenko Kyiv University identified. The existing IT infrastructure and the solutions of Grinchenko University is analyzed that can be the basis for the introduction of a «digital campus». The main components of the «digital campus» considered, which correspond to the implemented best solutions in the European educational space and at the same time satisfy the needs of the university. Analyzed the innovative solutions for the implementation of «digital campus», such as Almus Net, Classter, LMS 365, TESLA EDU, SMART HCM&LMS, ZEROBIT, and EXAMUS. The comparative analysis of the components of these solutions displayed for the construction of «digital campus». The main stages of implementation of the «digital campus» identified. Attention is paid to the fact that the construction of the digital campus should integrate the existing solutions as much as possible to ensure the comfort and convenience of participants in the educational process, implement new required solutions, each of which, thanks to unification into a single system, will ensure the functioning of a modern higher education institution, will work on its development and competitiveness. The created «digital campus» will ensure the functioning of the educational institution, the automation of all business processes, provide access to educational resources and facilitate successful management decisions.